Memória militante: a atuação das redes de preservação documental na salvaguarda dos arquivos das classes subalternas - Cotrim, Renata Aparecida (2022)
Based on the issues that involved the constitution of different archives of subaltern groups, more specifically the Brazilian labour movement, this research analyzed the foundation of the Archivio Storico del Movimento Operaio Brasiliano (ASMOB) as the result of the work of documentary preservation networks, internationally articulated, through their preservationist tradition within social activists and leftist organizations – mainly socialists, communists and anarchists – of documenting and keeping the records of the struggles and memories of its class since the beginning of the XX Century. With the study and crossexamination of the primary sources which constitute the different collections present at the ASMOB, the origin and actions of the above-mentioned networks can be acknowledged as being the main support for the safekeeping of important sets of documents reunited in Brazil and other countries. Through the investigation of fundamental relations – both political and personal – involved in the creation of these collections, it was possible to observe and understand the process of constructing a collective memory, and the struggle to preserve the history, and the memory, of these subaltern classes, especially, that of the Brazilian labour movement